The influence of corporate social responsibility on firm reputation with the moderating effect of personal employees' ethical value - Saeidi, Sayedeh Parastoo (2022)
This study attempts to investigate the conditional effects of the ethical values of employees and corporate social responsibility (CSR), as two possible influencing variables on a firm's reputation. Moreover, this research determines the moderating effect of ethical values of employees on the relationship of CSR with firm reputation. AMOS is used as a visual program in structural equation modelling in order to analyse and test the hypotheses suggested in this paper. Data were collected from 301 SMEs in industrial and service sectors, in Malaysia, using survey method through structured questionnaires with five-point Likert scales. According to the results, hypothesis of moderating effect of personal employees' ethical values (PEEV) on CSR and firm reputation in the industrial sector was rejected; whereas a conditional moderating effect of ethical values of employees on CSR and firm reputation was reported in the service sector. This shows that when companies rely more on human resources, a higher level of ethical values among employees leads to a higher level of reputation for the firm in society, even if CSR is at a low level at those companies.